Esophageal invasive acantholytic anaplastic Paget’s disease: report of a unique case - Lin, Dong-Liang (Int J Clin Exp Pathol, 2019)
Paget’s disease (PD) is an intraepithelial growth of neoplastic cells showing glandular differentiation. Primary esophageal PD is extremely rare, with only 14 cases reported to date. We report a case of esophageal PD in a 63-year-old man presenting with progressive dysphagia. On gross examination, the esophageal mucosa had a slightly mottled appearance and felt slightly thickened and indurated. Microscopically, the atypical tumor cells were mostly located in middle to basal cell layers of the squamous epithelium. Some tumor cells were difficult to be distinguished from normal squamous epithelium. Some regions of the lesion showed full-thickness cellular atypia with mitotic figures, and some tumor cells invaded through the basement membrane into the lamina propria, mimicking a squamous cell carcinoma. Acantholytic regions were prominent in the epithelium, and some gland-like clefts were formed. One recurrent laryngeal nerve lymph node showed metastatic foci. Immunohistochemically, tumor cells were positive for cytokeratin (CK) 7, CK8/18, carcinoembryonic antigen (CEA) and Her-2, but negative for CK5/6, p63, S-100 protein and HMB45, yielding the diagnosis of PD. This is the first case report of esophageal invasive Paget’s disease (invPD) and the first case report of esophageal acantholytic anaplastic Paget’s disease (AAPD).